2019
DOI: 10.5603/fhc.a2018.0021
|View full text |Cite
|
Sign up to set email alerts
|

Melanization of Bomirski hamster amelanotic melanoma cells (Ab line) depends on the type of culture medium

Abstract: Introduction. The effect of melanogenesis intensity on melanoma biology remains an open question, and the biological differences between melanotic and amelanotic melanoma cells have not yet been satisfactorily documented. As a result, the melanization of melanoma cells in in vitro cultures is not considered among experimental procedures. The aim of this study was to investigate the effect of the medium used to culture Bomirski amelanotic Ab melanoma cells on the melanogenesis process. Material and methods. Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(48 reference statements)
0
3
1
Order By: Relevance
“…2009). The presence of tyrosinase protein was confirmed in both Ab and B16F10 melanoma cells (Skoniecka et al 2018). Our observation did not confirm Kreider and Schmoyer's results which showed that ongoing melanization in B16 cells decreased proliferation in a significant way (Kreider and Schmoyer 1975).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…2009). The presence of tyrosinase protein was confirmed in both Ab and B16F10 melanoma cells (Skoniecka et al 2018). Our observation did not confirm Kreider and Schmoyer's results which showed that ongoing melanization in B16 cells decreased proliferation in a significant way (Kreider and Schmoyer 1975).…”
Section: Discussioncontrasting
confidence: 85%
“…Ab cells in DMEM were the amelanotic melanoma cells which exhibited the most darkening. The presence of melanin granules and tyrosinase activation were observed in Ab cells cultured in DMEM in our earlier studies (Skoniecka et al 2018). Morphological changes, decreasing cell numbers and significant displacement of cells from all cell cycle phases to the subG0/G1 fraction indicated Ab cell death.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is important to emphasize the possible chemotherapeutics and radiotherapy effect on melanogenesis, basic process for melanoma cells thus changing the tumor cells biology. 11,12 Vierne et al . reported an histologically different, mainly amelanotic mandibular metastasis 16 years after adjuvant radiotherapy treatment for primary cutaneous melanoma.…”
Section: Discussionmentioning
confidence: 99%